Phytochemical Composition of Zingiber Officinale Roscoe - Khaydarov Doston Bakhodirovich (Scholars Digest Publishing, 2023)
Ginger is rich in active ingredients such as phenolic and terpene compounds. Phenolic compounds in ginger are mainly represented by gingerols, shogaols and paradols. In fresh ginger, the main polyphenols are gingerols such as 6-gingerol, 8-gingerol and 10-gingerol. 6-Gingerol is the most pharmacologically active among these compounds. 6-Gingerol is the most pharmacologically active among these compounds.
Keywords: Ginger, Phenolic compounds in ginger, 6-gingerol, 8-gingerol and 10-gingerol.